The Effect of Hanging Ball Learning Method on Volleyball Smash Accuracy in Grade IX Students of MTs Hidayatul Islam Tanjungharjo - Farhan Abdur Roqib; Rohmad Apriyanto; Hasan Saifuddin (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Volleyball is a form of physical activity that can be utilized in physical education learning to develop students' basic motor skills, such as smash or passing abilities. The study aims to examine the effect of hanging ball learning on smash abilities in volleyball learning for ninth grade students of MTs Hidayatul Islam Tanjungharjo. The research problem begins with the low ability of students to smash accurately. This study uses a quantitative approach with a pre-experimental one group pretest-posttest design. The research sample consisted of 30 students selected using a simple random sampling technique. The research instrument was a test of smash ability to the target. The treatment was carried out for 4 meetings through hanging ball learning that trains leg muscle strength, improves shot accuracy, and hits with the highest range. The results of the analysis showed an increase in the average shooting score from 5.73 in the pretest to 12.50 in the posttest. The normality test showed that the data was normally distributed, while the results of the t-test (Paired Sample T-Test) obtained a Sig. (2-tailed) value <0.05, which means there was a significant difference between the pretest and posttest results. The findings indicate that hanging ball training is effective in improving smashing ability. Therefore, physical education teachers are advised to utilize hanging ball training as an engaging learning alternative that improves motor skills and fosters character values.